Frequency Analysis of Ocular Hypertension after Microinvasive Ultrasonic and Traditional Guillotine Vitrectomy 25G - B. M. Aznabaev; T. I. Dibaev; A. S. Dzinter; T. R. Mukhamadeev; A. Sh. Zagidullina (Oftalʹmologiâ)
Purpose. To compare the frequency of ocular hypertension in patients in the early postoperative period after microinvasive ultrasonic and 25G pneumatic guillotine vitrectomy.Patients and methods. The article presents the results of studying intraocular pressure (IOP) and the frequency of postoperative ophthalmohypertension in patients in the early postoperative period after microinvasive ultrasound and pneumatic guillotine 25G vitrectomy. We analyzed the data of 256 patients (256 eyes) — 158 women, 98 men who underwent vitreoretinal surgery for the pathology of the vitreomacular interface, retinal detachment, diabetic proliferative retinopathy, hemophthalmia at the Optimed, Ufa with a follow-up for 1 month. For tamponade, physiological saline, gas-air mixture, silicone oil, sterile air were used, depending on the nature and severity of vitreoretinal pathology. The mean age was 59.2 ± 12.5 years. In the main group, patients were operated with microinvasive ultrasonic vitrectomy 25G (n = 136), in the control group — using pneumatic guillotine vitrectomy 25G (n = 120). Non-contact tonometry (Nidek Tonoref 3, Japan) was performed with a correction according to measurements of the central thickness of the cornea on a reflective microscope with pachymetry function (Tomey, ЕМ-3000, Japan) before surgery and on days 1, 7, and 30 after vitrectomy. Exclusion criteria from the study were: the presence of symptomatic ophthalmohypertension, glaucoma, traumatic injury to the angle of the anterior chamber, immature and mature cataracts, lens luxation. IOP indicators in both groups at different times of the early postoperative period (days 1, 7, 30) did not differ statistically significantly.Results. The frequency of ocular hypertension on day 7 in the main group was 20.6 %, in the control group — 20 %, and on day 30 — 11 % and 10 %, respectively (the difference between the groups was not statistically significant, p > 0.05). The highest IOP values were observed with silicone oil tamponade.Conclusion. The first analysis of the frequency of ocular hypertension in patients after microinvasive ultrasonic vitrectomy 25G did not reveal statistically significant differences with pneumatic guillotine vitrectomy for various types of tamponade.